Estimation of Subsurface Structure Based on Mocrotremor, Bore Hole Observations and Stochastic Strong Ground Motion Simulations in Palu City, Central Sulawesi, Indonesia: A Validation and Sensitivity Study on The 23 January 2005 (Palu) Earthquake - Pyi Soe Thein, Pyi Soe Thein (2014)
In this study, we investigated the subsurface and strong ground motion parameters for Palu City. On of major structures in Central Sulawesi is the Palu-Koro Fault System. Several powerful earthquakes have struck along the Palu_Koro during recent years, one of the largestof which was an M 6.3 event that occured on January 23, 2005 and caused several casualties.